RNA-transfection of γ/δ T cells with a chimeric antigen receptor or an α/β T-cell receptor: a safer alternative to genetically engineered α/β T cells for the immunotherapy of melanoma - Harrer, Dennis C.; Simon, Bianca; Fujii, Shin-Ichiro; Shimizu, Kanako; Uslu, Ugur; Schuler, Gerold; Gerer, Kerstin F.; Hoyer, Stefanie; Dörrie, Jan; Schaft, Niels (BMC Cancer, 2017)
BACKGROUND: Adoptive T-cell therapy relying on conventional T cells transduced with T-cell receptors (TCRs) or chimeric antigen receptors (CARs) has caused substantial tumor regression in several clinical trials. However, genetically engineered T cells have been associated with serious side-effects due to off-target toxicities and massive cytokine release. To obviate these concerns, we established a protocol adaptable to GMP to expand and transiently transfect γ/δ T cells with mRNA. METHODS: PBMC from healthy donors were stimulated using zoledronic-acid or OKT3 to expand γ/δ T cells and bulk T cells, respectively. Additionally, CD8+ T cells and γ/δ T cells were MACS-isolated from PBMC and expanded with OKT3. Next, these four populations were electroporated with RNA encoding a gp100/HLA-A2-specific TCR or a CAR specific for MCSP. Thereafter, receptor expression, antigen-specific cytokine secretion, specific cytotoxicity, and killing of the endogenous γ/δ T cell-target Daudi were analyzed. RESULTS: Using zoledronic-acid in average 6 million of γ/δ T cells with a purity of 85% were generated from one million PBMC. MACS-isolation and OKT3-mediated expansion of γ/δ T cells yielded approximately ten times less cells. OKT3-expanded and CD8+ MACS-isolated conventional T cells behaved correspondingly similar. All employed T cells were efficiently transfected with the TCR or the CAR. Upon respective stimulation, γ/δ T cells produced IFNγ and TNF, but little IL-2 and the zoledronic-acid expanded T cells exceeded MACS-γ/δ T cells in antigen-specific cytokine secretion. While the cytokine production of γ/δ T cells was in general lower than that of conventional T cells, specific cytotoxicity against melanoma cell lines was similar. In contrast to OKT3-expanded and MACS-CD8+ T cells, mock-electroporated γ/δ T cells also lysed tumor cells reflecting the γ/δ T cell-intrinsic anti-tumor activity. After transfection, γ/δ T cells were still able to kill MHC-deficient Daudi cells. CONCLUSION: We present a protocol adaptable to GMP for the expansion of γ/δ T cells and their subsequent RNA-transfection with tumor-specific TCRs or CARs. Given the transient receptor expression, the reduced cytokine release, and the equivalent cytotoxicity, these γ/δ T cells may represent a safer complementation to genetically engineered conventional T cells in the immunotherapy of melanoma (Exper Dermatol 26: 157, 2017, J Investig Dermatol 136: A173, 2016).
EVALuna2:34316